Photoanthropometric study: are non-professional photographs suitable for objective and reliable analysis of facial features? - Egle Stukaite-Ruibiene; Stefanie Ritz-Timme; Cristina Cattaneo; Zuzana Obertova; Renata Simkunaite-Rizgeliene; Arunas Barkus; Janina Tutkuviene (Taylor & Francis Group, 2024)
Background The face has been widely investigated using professionally taken frontal and lateral photographs, however, there is a lack of studies of non-professional facial photographs. It is not known if they could be suitable for facial analysis. The analysis of non-professional photographs could allow the performance of cost- effective longitudinal studies.Aim To determine if non-professional photographs could be used for a reliable analysis of facial features.Subjects and methods The frontal profiles of 18-21-year-olds (35 males, 39 females) were measured by direct anthropometry, in addition, professional photographs were taken and non-professional photographs were obtained. Anthropometric landmarks were superimposed on those photographs. The indices calculated on the basis of the measurements of direct anthropometry and both types of photographs were compared.Results The comparison of the measurements of direct anthropometry and professional photographs showed no difference between 14 out of 25 male and 10 out of 25 female facial indices (p > 0.05) after comparing the results of direct anthropometry with those of non-professional photographs, no difference was found in 8 out of 25 male and 7 out of 25 female indices. These indices were mostly composed of vertical parameters and eye measurements.Conclusion Vertical facial dimensions and eye measurements may not only be used interchangeably for both facial photographs and direct anthropometry, but may also be suitable for objective and reliable facial analyses.